Functional products fortified with probiotic LAB isolated from Egyptian dairy sources showed hypolipidemic effects in Albino rats. - Amira M G Darwish; Marwa G Allam; Enaam S Shokery; Eman H E Ayad (PLoS ONE)
Biological food industry has increased economic importance of new Lactic Acid Bacteria (LAB) with functional aspects such as health promoting and enhanced sensorial traits. The objectives of the present study were the isolation and genotypic characterization (16S rRNA) of new LAB isolates from Egyptian Laban Rayeb, Zabady and mothers' breast milk as potential probiotics. Strains were in vitro and in vivo evaluated for their safety and probiotic health promoting traits in Albino rats then applied into two types of functional dairy products. Three strains Streptococcus thermophilus MH422542, Enterococcus faecium MH422543 and Lactococcus lactis subsp lactis MH422545, were selected from a pool of 82 strains. St. thermophilus showed proteolytic activity and production of Exopolysaccharides (EPS). When evaluated in animal models; the strains showed hypolipidemic effects especially E. faecium that reduced atherogenic indices up to 88%. The strains modulated the gut microbiota by reducing Staphylococcus sp. and coliforms with no adverse effects either on blood parameters, antioxidant enzymes, cancer markers or hepatocytes histological examination. Only E. faecium MH422543 showed an immune response by increased white blood cells (WBC) while lymph and platelets values were not affected. The probiotic strains approved their convenience as starter/ adjunct cultures and enhanced organoleptic properties of the fermented dairy products.